GAMBARAN KADAR HBA1C PADA PENDERITA DIABETES MELITUS DI KLINIK DIABETES DHARMA MEDAN - Thomas Silangit; Endy Juli Anto (Universitas Methodist Indonesia, 2018)
Background. Type 2 diabetes mellitus (T2DM) is something that cannot be stated in one clear and concise answer but in general it can be said as a collection of anatomic and chemical problems resulting from a number of factors which obtain absolute or relative insulin deficiency and impaired insulin function. Insulin is a hormone which consists of a series of amino acids, produced by beta cells of the pancreas gland. Under normal circumstances, if there is beta cell stimulation, insulin is synthesized and then secreted into the blood according to the body's needs for the regulation of blood glucose. The glycosylated hemoglobin test, also known as glycohaemoglobin, or glycosylated haemoglobin (HbA1c), is a method used to assess the effect of changes in therapy 8-12 weeks earlier. The purpose of this study was to determine the description of HbA1c levels in the Medan Diabetes Dharma Clinic in 2016-2017 Methods. This study used a descriptive research method with a cross sectional design. This research was conducted in 2016-2017 at the Diabetes Dharma Clinic in Medan. By using total sampling technique, with a sample of 200 patients who have met the criteria. Data is collected by retrieving data from medical records that perform HbA1c checks, then processing and analyzing data. Result. Examination of the highest frequency of HbA1c levels in the age group> 40 years was 180 people (90%). Based on gender, the frequency is more for men, which is 121 people (60%) compared to women, which is 79 people (39.5%). The proportion of the biggest sufferers of diabetes mellitus is 181 people (90.5%) with HbA1c levels of more than 6.4%. The mean level of HbA1c values ​​in patients with diabetes mellitus was 9.295% (2.3) and the highest value was 18.3% and the lowest value was 5.4%. Summary. In this study that T2DM increased at the age above 40 years and the frequency of men was more than women. HbA1c levels at the Diabetes Dharma Clinic in Medan are still uncontrolled.